A review of supercritical technologies for lipid-based biofuels production: The glycerol-free processes - Sakdasri, Winatta; Komintarachat, Cholada; Sawangkeaw, Ruengwit; Ngamprasertsith, Somkiat (My University, 2021)
Supercritical transesterification of lipid-based biomasses, a recent technique to produce biofuel without a catalyst, is discussed. This review focused on a glycerol-free process. The supercritical reactants include dimethyl carbonate, diethyl carbonate, methyl acetate, ethyl acetate (ETA), and methyl tert-butyl ether. The by-products from the glycerol-free process can improve both the quantity and quality of the resultant biofuel. This review suggests that supercritical transesterification of lipid-based biomasses using ETA as a co-reactant can provide the most valuable advantages, as involves inexpensive and renewable resources, which are important for biofuel production and sustainability.
Keywords: Biofuel; Biomass; Glycerol; Oxygenated fuel; Supercritical fluids